The 7.2 ka climate event: Evidence from high-resolution stable isotopes and trace element records of stalagmite in Shuiming Cave, Chongqing, China. (January 2020) - Feng, Xiangxiang; Yang, Yan; Cheng, Hai; Zhao, Jingyao; Kong, Xinggong; Zhang, Ping; He, Zhili; Shi, Xiao; Edwards, R Lawrence
Speleothem records have radically changed our understanding of the paleo Asian monsoon (AM), but explanations for Asian summer monsoon (ASM) variations in the Holocene period are usually based on single proxy records, such as oxygen isotope (δ 18 O). The application of multi-proxy records to the study of the forcing mechanism and internal structure of climate events is more comprehensive and accurate in the analysis of paleoclimates than using single proxy records. Therefore, a multi-proxy speleothem record of weak ASM events in 8.0–7.0 BP from Chongqing, which showed a dry southwestern China during weak ASM episodes, was reported. The analysis of multi-proxy records of SMY2 stalagmite indicated that the beginning of the '7.2 ka event' was at 7.29 ± 0.03 ka BP, and its culmination was at 7.1 ± 0.04 ka BP. Thus, this event lasted nearly 200 a, and the main drought period lasted 50 a. Power spectrum analysis showed a significant 61 a cycle signal during the study period in the δ 18 O record of SMY2, which coincided with the Atlantic multidecadal oscillation activity (AMOC) cycle. This study demonstrates that the ASM during 8.0–7.0 ka BP is strongly correlated with the changes in solar activity and also sensitive to the southward shift of Intertropical Convergence Zone (ITCZ) and AMOC cycle.